2020
DOI: 10.1097/md.0000000000021413
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and related factors in frontline clinical nurses fighting COVID-19 in Wuhan

Abstract: The aim of this study was to examine the anxiety status of the frontline clinical nurses in the designated hospitals for the treatment of coronavirus disease 2019 (COVID-19) in Wuhan and to analyze the influencing factors, to provide data for psychologic nursing. This study used a cross-sectional survey design and convenience sampling. The questionnaires were completed by 176 frontline clinical nurses. Anxiety was determined using the Hamilton anxiety scale. General data were collected using a surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
2
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 3 publications
(3 reference statements)
3
49
2
4
Order By: Relevance
“…The overall pooled point estimates of prevalence for anxiety varied between 8% and 91%, which was reported by 73 studies [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [28] , [29] , [30] , 32 , 34 , 35 , [37] , [38] , [39] , [42] , [43] , [44] , [45] , [46] , 48 , 49 , 51 , [53] , [54] , [55] , [56] , [57] , 62 , [64] , [65] , [66] , [67] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] ,…”
Section: Resultsmentioning
confidence: 99%
“…The overall pooled point estimates of prevalence for anxiety varied between 8% and 91%, which was reported by 73 studies [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [28] , [29] , [30] , 32 , 34 , 35 , [37] , [38] , [39] , [42] , [43] , [44] , [45] , [46] , 48 , 49 , 51 , [53] , [54] , [55] , [56] , [57] , 62 , [64] , [65] , [66] , [67] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] ,…”
Section: Resultsmentioning
confidence: 99%
“…Anxiety: A total of 21 studies [ 9 , 10 , 12 , 28 - 34 , 37 , 38 , 40 - 48 ] assessed the prevalence of anxiety among nurses and its severity level was appraised by eight studies [ 10 , 31 , 33 , 34 , 37 , 40 , 46 , 48 ]. The overall pooled prevalence of anxiety was 33% (95% CI = 24%-43%) with substantial heterogeneity ( I 2 = 99.4%, P < 0.01) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The study sample in this study, medical assistants, were mainly women working in an outpatient setting and performing non-physician tasks. Several studies among medical staff during the SARS-CoV-2 pandemic have found women to suffer from higher levels of distress than men [ 5 , 24 ]. Other studies reported nursing staff to feel more anxious during the pandemic than physician staff [ 22 ].…”
Section: Discussionmentioning
confidence: 99%